Interweaving Creative Critical Sense-Making through a Body of Koloa: An Exploratory Examination of Falanoa as an Intergenerational Arts-Based Research Method - Dyck, Dagmar; Scott Fanamanu, Caroline (Art/Research International)

(untitled) (University of Alberta, 2024)
Storytelling through the arts is embedded in Pacific cultural ways and is meaningfully expressed by interweaving history, genealogy, cultural values, and beliefs. My investigation into Pasifika students’ success as Pasifika in visual arts was revealed through the students’ artworks and stories. Visual art teachers’ beliefs, attitudes and pedagogical practices were also examined to illuminate the critical role they play in affirming Pasifika student success as Pasifika. The inclusion of my own experiences and artworks as a visual artist of Tongan and German descent, grounds the research project and offers voice to my creative critical sense-making process. This article also presents an exploratory examination of falanoa, alongside Caroline Scott Fanamanu’s analysis, as an intergenerational arts-based research method, specifically in the context of my own body of koloa, a personal collection of treasured artworks generated across a 30-year period. Recognising my duality of distinct ancestral worlds, this article suggests that falanoa can be a valuable method for arts-based research, particularly in the context of creative critical sense-making, cultural preservation, and intergenerational knowledge.